2011
DOI: 10.1002/app.34126
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of a novel graft copolymer containing carboxyl groups and its application to extract uranium(VI) from aqueous media

Abstract: A novel poly(methacrylic acid)-grafted-cellulose/bentonite (Cellu-g-PMAAc/Bent) superabsorbent composite was prepared through graft copolymerization reaction among cellulose, methacrylic acid, and bentonite in the presence of N,N 0 -methylenebisacrylamide as a crosslinker and potassium peroxydisulphate as an initiator. The structural and morphological characteristics of the graft copolymer were determined using Fourier transform infrared spectra, scanning electron microscopeenergy dispersion analysis, and X-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…The main reason for this selection is the susceptibility of layered clays to organic/inorganic modifications apart from their large internal surface area. But adsorption simply transfer contaminants from one phase to another which demands further chemical treatment for the recovery of the adsorbent material [13,14]. Also, excessive usage of adsorbents gradually leads to problems with landfill.…”
Section: Introductionmentioning
confidence: 99%
“…The main reason for this selection is the susceptibility of layered clays to organic/inorganic modifications apart from their large internal surface area. But adsorption simply transfer contaminants from one phase to another which demands further chemical treatment for the recovery of the adsorbent material [13,14]. Also, excessive usage of adsorbents gradually leads to problems with landfill.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review of uranium recovery technologies by Kim et al (2013b) identified uranium adsorption by chelating polymers to be the most promising in terms of cost, adsorption capacity, and environmental footprint (Zhang et al, 2003;Seko et al, 2003;Anirudhan et al, 2011). Other techniques, including membrane filtration, coagulation, and precipitation were found to have issues such as high operating costs, durability, or toxicity (Kanno, 1984;van Reis and Zydney, 2007;Tularam and Ilahee, 2007).…”
Section: Seawater Uranium Extractionmentioning
confidence: 99%
“…Extraction of uranium from seawater has been researched for decades, with one of the first studies conducted by Davies et al (1964) after World War II in an effort to secure uranium supply for Britain at a time when the production of uranium was uncertain. A recent review of uranium recovery technologies by Kim et al (2013b) identified uranium adsorption by chelating polymers to be the most promising in terms of cost, adsorption capacity, and environmental footprint (Zhang et al, 2003;Seko et al, 2003;Anirudhan et al, 2011). Other techniques, including membrane filtration, coagulation, and precipitation were found to have issues such as high operating costs, durability, or toxicity (Kanno, 1984;van Reis and Zydney, 2007;Tularam and Ilahee, 2007).…”
Section: Seawater Uranium Extractionmentioning
confidence: 99%